Synergistic promoting effect of ball milling and KF–alumina support for the green synthesis of benzothiazinones. Issue 5 (3rd February 2016) - Sharifi, Ali; Ansari, Mohammad; Darabi, Hossein Reza; Abaee, M. Saeed
Graphical abstract: Highlights: Benzothiazinones are synthesized under solvent-free and ball mill conditions. Reactions take place by using inexpensive KF–Al2 O3 support. The catalyst is recyclable. Synthesis of several derivatives shows the generality and efficiency of the method. Abstract: A solvent-free procedure was developed for the reaction of 2-aminothiophenols with 2-bromoalkanoates, where KF–Al2 O3 support and ball milling cooperatively lead to a green and efficient synthesis of several benzothiazinone derivatives in good to excellent yields. The catalyst could be recycled in further reactions while maintaining its activity.